Museum-based therapeutic interventions in pediatric oncology: the ETRU4KIDS experience as a model for hospital wellness enhancement - Ruggiero, Antonio; Guido, Antonella; Lecce, Vittoria; Montuori, Francesca; Toniolo, Luana; Osanna, Massimo (Frontiers in Education, 2025)
Pediatric oncology patients face multifaceted challenges extending beyond disease pathophysiology and therapeutic interventions. Cancer treatment frequently disrupts fundamental developmental processes, compromising physical and emotional functioning, social relationships, and cognitive maturation. While conventional biomedical approaches remain essential for disease control, they inadequately address the comprehensive psychosocial needs of children requiring sustained therapeutic support. To address these unmet psychosocial needs, the initiative draws on principles from museum education and arts-in-health, integrating cultural engagement as a therapeutic strategy within pediatric oncology care. The ETRUscan museum For Kids (ETRU4KIDS) program represents an innovative interdisciplinary collaboration between the Pediatric Oncology Department at Fondazione Gemelli IRCCS and Rome’s National Etruscan Museum of Villa Giulia. This initiative demonstrates how cultural institutions can serve as therapeutic adjuvants, providing evidence-based psychosocial interventions that specifically target emotional processing, quality of life optimization, and psychological resilience enhancement tailored to pediatric developmental requirements. The protocol incorporates structured museum experiences, interactive educational workshops, and Etruscan-inspired ceramic art therapy sessions designed to create therapeutic environments where cultural engagement and creative expression facilitate psychological healing. A prospective observational study enrolled 25 pediatric oncology patients. Outcome measures utilized validated assessment instruments including the Visual Analogue Scale (VAS), Arts Observation Scale (ArtsObS), and Pediatric Quality of Life Inventory (PedsQL). Results demonstrated statistically significant improvements: emotional wellbeing showed VAS score increases of 3.2 ± 1.4 points (p < 0.001), creative engagement reflected 42% ArtsObS score enhancement (p < 0.01), and overall quality of life exhibited 18% PedsQL improvement (p < 0.01). ETRU4KIDS provides a replicable framework for integrating cultural-artistic interventions into comprehensive pediatric oncology care.